Ionic liquid-based dispersive liquid-liquid microextraction combined with functionalized magnetic nanoparticle solid-phase extraction for determination of industrial dyes in water - Liang, Ning (Sci Rep, 2017)
N-butyl pyridinium bis((trifluoromethyl)sulfonyl)imide ([Hpy]NTf(2)) functionalized core/shell magnetic nanoparticles (MNPs, Fe(3)O(4)@SiO(2)@[Hpy]NTf(2))) were prepared and applied as an adsorbent for magnetic solid phase extraction (MSPE) of three commonly used industrial dyes including malachite green, crystal violet and methylene blue. Extraction solution was mixed with 100 mg extraction material of Fe(3)O(4)@SiO(2)@[Hpy]NTf(2), and 1 mL of acetonitrile was used to elute target analytes for further extraction and purification. [Hpy]NTf(2) was used as extraction solution, and 500 μL methanol was selected as dispersive solvent in ionic liquid (IL) dispersive liquid–liquid microextraction (DLLME) method. After sonication for 5 min and centrifugation at 447 g for 10 min, 20 μL of sedimented phase was injected into HPLC-UV system. The limit of detection (LOD) and limit of quantification (LOQ) of current method were 0.03 and 0.16 μg·L(−1), respectively, which indicated the sensitivity was comparable or even superior to other reported methods. The relative recoveries of the target analytes ranged from 86.1% to 100.3% with relative standard deviations between 0.3% and 4.5%. The developed method has been successfully applied to determine the level of three industrial dyes in different water samples.